A Narrative Review on Advancing Pediatric Oral Health: Comprehensive Strategies for the Prevention and Management of Dental Challenges in Children - Sung-Ying Han; Chia-Lin Chang; Yung-Li Wang; Ching-Shuen Wang; Wei-Ju Lee; Thi Thuy Tien Vo; Yuh-Lien Chen; Chueh-Yi Cheng; I-Ta Lee (Children)
Oral health is fundamental to overall well-being, especially in childhood, when dental structures and lifelong habits are established. This review provides a comprehensive analysis of children’s dental development, common oral health challenges, and evidence-based preventive strategies. Key topics include the mechanisms of tooth development, the eruption processes of primary and permanent dentition, and the management of developmental abnormalities. The prevalence, risk factors, and health impacts of dental caries in children are examined, underscoring the need for early intervention and targeted prevention. This review evaluates the effectiveness of preventive measures such as dental sealants, fluoride varnishes, and fluoride mouth rinses while highlighting the influence of dietary habits, toothbrush selection, and parental involvement on oral health outcomes. Additionally, it explores the synergistic benefits of combining preventive approaches, such as the concurrent use of dental sealants and fluoride applications, which have demonstrated superior caries prevention compared to either method alone. The effectiveness of these strategies is analyzed across different age groups, from early childhood to adolescence, with tailored recommendations for each developmental stage. Furthermore, the role of education, policy interventions, and community-based programs in addressing oral health disparities is discussed. By integrating developmental insights with epidemiological data and clinical evidence, this review provides a comprehensive framework for advancing pediatric dentistry, informing best practices, and enhancing preventive strategies to reduce the burden of oral diseases in diverse pediatric populations.